Performance, Politics, and Historiography in and out of Time: American Responses to the Paris Commune - Loren Kruger (Pamiętnik Teatralny, 2021)
American echoes of the Paris Commune have been muffled by the nation’s obsession with freedom at the expense of solidarity, but performative responses to social upheaval, including drama, parades, and protests, have tested the boundaries of public space and multiple temporalities from 1871 to 2021. This article notes traces of the Commune in the writings and performances of nineteenth century American anarchists but analyzes this legacy primarily in the 2012 performance of Brecht’s The Days of the Commune (1949) at New York sites claimed by the Occupy Movement in 2011. It also uses the argument of Brecht’s contemporary Ernst Bloch for cultural action grounded in an understanding of historical disappointment to anticipates setbacks while maintaining hope for future revolution. The paper delineates five theses on the politics of time: 1) the dramatic appeal of the clean break hides the tension between gradual evolution and a sudden event that ruptures the long span of history (Badiou); 2) historiography, the narrative that turns data into evidence, challenges the illusion of objectivity and thus a simple split between timely intervention and untimely interference with the established order (Nietzsche); 3) ana-chronology, the logic of untimeliness reads contemporaneity as companionship between events and agents across different times and places (Barthes); 4) recollecting history requires acts of forgetting, which shatter the constraints of the past to meet demands of the present (Renan, Nietzsche); 5) the politics of time entails the politics of place and thus requires the analysis of multiple temporalitieslayered on one site as well as political acts and performance in distinct places.